The impact of the Troubles on the Republic of Ireland, 1968-79 : boiling volcano? - Hanley, Brian (Manchester Political Studies, 2018)
This book tells the story of how the war in Northern Ireland threatened to engulf the Republic. It explains how popular opinion responded to the crisis from marching in solidarity with nationalists to increasing disengagement and fear.